Place recognition monitored by location-driven operant responding during passive transport of the rat over a circular trajectory - Klement, D; Bures, J (Proceedings of the National Academy of Sciences of the United States of America, 2000)
Spatial memory of animals is usually tested in navigation tasks that do not allow recognition and recall processes to be separated from the mechanisms of goal-directed locomotion. In the present study, place recognition was examined in rats (n = 7) confined in an operant chamber mounted on the periphery of a slowly rotating disk (diameter 1 m, angular velocity 9 degrees /s). The animals were passively transported over a circular trajectory and were rewarded for bar pressing when they passed across a 60 degrees -wide segment of the path. This segment was recognizable with reference to room landmarks visible from the operant box. Responding defined in the coordinate system of the room increased when the chamber entered the 60 degrees -wide approach zone, culminated at the entrance into the reward sector, was decreased inside it by eating the available reward, and rapidly declined to zero at the exit from this zone. When reward was discontinued, the skewed response distribution changed into a symmetric one with a maximum in the center of the reward sector. With advancing extinction, the response peak in the reward sector decreased in most rats proportionally to the overall decline of bar pressing. The rewarded and nonrewarded response patterns indicate that passively transported rats can recognize their position in the environment with an accuracy comparable to that of actively navigating animals and that location-driven operant responding can serve as a useful tool in the analysis of the underlying neural mechanisms.
Keywords: Pattern Recognition, Visual; chování zvířat; potravinová deprivace; prostorové chování; učení; Rotation; Orientation; krysa rodu Rattus; zvířata; Rats, Long-Evans; životní prostředí - projekt; rozpoznávání obrazu; Food Deprivation; Male; Learning; orientace; rotace; potkani Long-Evans; Rats; Animals; Environment Design; Spatial Behavior; mužské pohlaví; Behavior, Animal